DESIGNING A BOUTIQUE HOTEL IN KESAWAN WITH AN ADAPTIVE REUSE APPROACH - Hutabarat, Mitha Sintia; Hadinugroho, Dwi Lindarto (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2024)
The tourism industry in Medan City has grown rapidly. This progress has an influence on the increasing need for temporary housing. Boutique hotel is one of the efforts to provide lodging facilities with certain services, such as accommodation in accordance with tourism in the local culture. By considering boutique hotel design ideas influenced by the attractiveness of Kesawan which is a cultural heritage area. The design challenge of a boutique hotel in Kesawan is to create the idea of harmony between human habitation and the surrounding culture, so that the design not only meets the accommodation needs but also introduces Kesawan to tourists.